SYNTHESIS AND CHARACTERIZATION OF ESTER PRODRUG OF MECLOFENAMIC ACID FOR REDUCTION OF ULCEROGENECITY - Niraj Kumar; Julekha Siddiqui; Kavita R. Loksh (Current Research in Pharmaceutical Sciences, 2025)
The research studies also reported that the of the ester prodrugs are for enhancing the anti-inflammatory activity and for reduction of ulcerogenic effects of NSAIDs. Also the studies attempted to evaluate the pharmacokinetics of the prodrugs by in-vitro methods. The inflammation induced by carrageenan that is an acute model. The carriers used in research work, sesamol, umbelliferone and thymol, also produced anti-inflammatory activity and antioxidant effects .Therefore, overall, synthesized products showed synergistic anti-inflammatory activity. The natural phenolic antioxidants for synthesizing the ester prodrugs are sesamol, 4- methyl umbelliferone and thymol and that itself showed various pharmacological activities.